2012
DOI: 10.5513/jcea01/13.3.1066
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of nitrogen leaching and nitrate concentration in a long-term field experiment

Abstract: The effects of organic and mineral nitrogen fertilization on nitrogen leaching and nitrate concentration in percolated water were simulated using the CANDY model. In a long-term IOSDV field experiment carried out from 1983 to the present in Lukavec, Czech Republic, increasing nitrogen rates from 0 kg to 200 kg N*ha-1 in mineral fertilizers were combined with the application of farmyard manure or straw, the control treatment was without organic fertilization. The simulation results of four rotations in the year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Long‐term crop production experiments provide an invaluable resource for scientists to assess production stability and crop yield × climate interactions, which are essential to crop modeling (Acock & Acock, 1991; Army & Kemper, 1991; Puntel et al., 2016). In addition, current and archived soil and plant samples provide a resource for scientists from diverse disciplines to quantify treatment effects on soil properties and processes including soil fertility (Davis et al., 2003; Girma et al., 2007; Overman & Scholtz, 2002), soil biology and organic matter (Dick, 1992; Eivazi, Bayan, & Schmidt, 2003; Miles & Brown, 2011; Nafziger & Dunker, 2011; Paustian, Elliott, & Carter, 1998), soil physical properties (Blanco‐Canqui & Schlegel, 2013), soil erosion (Gantzer, Anderson, Thompson, & Brown, 1991), and environmental quality (Haberle & Kas, 2012; Hansen & Djurhuus, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term crop production experiments provide an invaluable resource for scientists to assess production stability and crop yield × climate interactions, which are essential to crop modeling (Acock & Acock, 1991; Army & Kemper, 1991; Puntel et al., 2016). In addition, current and archived soil and plant samples provide a resource for scientists from diverse disciplines to quantify treatment effects on soil properties and processes including soil fertility (Davis et al., 2003; Girma et al., 2007; Overman & Scholtz, 2002), soil biology and organic matter (Dick, 1992; Eivazi, Bayan, & Schmidt, 2003; Miles & Brown, 2011; Nafziger & Dunker, 2011; Paustian, Elliott, & Carter, 1998), soil physical properties (Blanco‐Canqui & Schlegel, 2013), soil erosion (Gantzer, Anderson, Thompson, & Brown, 1991), and environmental quality (Haberle & Kas, 2012; Hansen & Djurhuus, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1942, 13 long-term replicated studies were initiated with a broad range of soil and crop management treatments. In addition to the development of practical crop productivity information, these long-term studies provided a resource for scientists from diverse disciplines evaluating treatment eff ects on numerous soil properties and processes including soil erosion (Gantzer et al, 1991), soil biology and organic matter (Miles and Brown, 2011;Paustian et al, 1998;Dick, 1992), soil fertility (Girma et al, 2007;Davis et al, 2003;Overman and Scholtz, 2002), soil physical properties (Blanco-Canqui and Schlegel, 2013), and environmental quality (Haberle and Kaš, 2012;Hansen and Djurhuus, 1996).…”
mentioning
confidence: 99%
“…Lukavec's soil and climate conditions (Table A1) and the effect of the treatment on the root density and depth suggest a greater risk of unused nitrate N leaching under the root zone in comparison to deep soils, with their greater water capacity and better root growth [13]. Káš et al (2019) found higher wheat yields in those years that had higher precipitation at Lukavec in comparison to Ivanovice; this was found in the long-term International Organic Nitrogen Long-term Fertilization Experiment (IOSDV) [7], which suggested complex interactions between water supply effects and leaching, growth, and nutrient depletion or demand.…”
Section: Potential For the Depletion Of Water And Leached Nutrients Fmentioning
confidence: 99%
“…The importance of data from LTEs has been increasingly 2 of 15 appreciated in light of the growing concerns about the sustainability of agro-ecosystems and soil quality, with increasing losses of nutrients, surface and groundwater pollution, and the transfer of heavy metals and pesticides to crops. More recently, discussions have also taken place regarding the impacts of climate change and possible approaches to drought adaptation [1,13,14]. The analysis and prediction of the impacts of crop systems on the long-term changes in soil organic matter to improve soil quality and to enhance the carbon sink properties of soils are not possible without data from long-term multisite field experiments that apply different rates of mineral and organic fertilizers [1,2,6,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%